INTERLANGUAGE: GRAMMATICAL ERRORS ON STUDENTS’ RECOUNT TEXTS (A Case Study of First Year of MAN 2 Banjarnegara in the Academic Year 2014/2015) (ELT Forum: Journal of English Language Teaching, 2015)
Differences between Indonesian and English language makes students often feel difficult in learning English especially in terms of grammar. Those difficulties tend to lead students to make errors in building English sentences. However, errors are actually natural because they are regarded as developmental stage to gain English competence, and errors are result from the students’ efforts to find ways of solving their problems. Those ways are called interlanguage. This study aims to find out the grammatical errors that students make in writing recount text and the interlanguage processes happen in it. The collecting data was done through writing recount text task to get kinds of errors data made by the students, and interview for getting interlanguage data happen to the students. The analysis steps started from identifying the errors, categorizing them into four categorizations of errors, and triangulating the errors with other supporting data. It reveals that students tend to make the errors omission, addition, misinformation, and misordering. The interlanguage processes happened are systematicity, permeability, fossilization consisting of language transfer, transfer of training, strategy of second language learning, and overgeneralization.